A Juridical Analysis of the Cancellation of Registered Trademarks Due to Non-Use: A Comparative Study of Indonesian and UK Law: Analisis Yuridis Terhadap Penghapusan Merek Terdaftar Akibat Tidak Digunakan: Perbandingan Hukum Indonesia dan Inggris - Kurniawan, Cicelly Chiesa; Gunadi, Ariawan (Rechtsidee, 2025)
General background: Legal protection of trademarks is fundamental to ensuring fairness and business certainty because exclusive rights apply only when marks are continuously used. Specific background: In Indonesia, cancellation of trademarks due to non-use for three consecutive years under Article 74 of Law No. 20/2016 remains challenging despite clear statutory provisions. Knowledge gap: Inconsistent judicial interpretations and the absence of uniform evidentiary standards create ongoing legal uncertainty. Aims: This study examines Indonesia’s mechanism for cancelling unused trademarks and compares it with the United Kingdom’s revocation system. Results: The findings show that Indonesia faces difficulties in proving non-use and maintaining consistent legal reasoning, while the UK—through the Trademarks Act 1994—implements structured administrative procedures, defined evidentiary criteria, and opportunities for non-litigation resolution. Novelty: This research offers a detailed comparative analysis that exposes procedural weaknesses in Indonesia when contrasted with a more mature and transparent system. Implications: The study suggests that Indonesia must strengthen evidentiary standards and refine administrative processes to enhance legal certainty, prevent passive monopolies, and reinforce effective trademark protection in modern commerce. Highlights: Focuses on cancellation of registered trademarks due to non-use in Indonesia and the UK. Identifies legal uncertainty in Indonesia from inconsistent interpretation of “three consecutive years” and proof standards. Highlights the UK’s clearer, more structured revocation procedures as a model for improving Indonesian law. Keywords: Trademark Cancellation, Non-Use, Legal Protection, Revocation